2017 IEEE International Conference on Systems, Man, and Cybernetics (SMC) 2017
DOI: 10.1109/smc.2017.8122658
|View full text |Cite
|
Sign up to set email alerts
|

Automatic response assessment in regions of language cortex in epilepsy patients using ECoG-based functional mapping and machine learning

Abstract: Abstract-Accurate localization of brain regions responsible for language and cognitive functions in Epilepsy patients should be carefully determined prior to surgery. Electrocorticography (ECoG)-based Real Time Functional Mapping (RTFM) has been shown to be a safer alternative to the electrical cortical stimulation mapping (ESM), which is currently the clinical/gold standard. Conventional methods for analyzing RTFM signals are based on statistical comparison of signal power at certain frequency bands. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In general, with AT-AR 3 -LF 2 is our best performing model with values >80% for all performance metrics including accuracy, sensitivity and specificity. In a feasibility study toward using machine learning for ECoG-FM, a random forest classifier was used in detecting positive and negative response channels with an accuracy of 78% (RaviPrakash et al, 2017). Traditionally, the accuracy of ECoG-FM is high for mapping sensory and motor function, but relatively low for language modality.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, with AT-AR 3 -LF 2 is our best performing model with values >80% for all performance metrics including accuracy, sensitivity and specificity. In a feasibility study toward using machine learning for ECoG-FM, a random forest classifier was used in detecting positive and negative response channels with an accuracy of 78% (RaviPrakash et al, 2017). Traditionally, the accuracy of ECoG-FM is high for mapping sensory and motor function, but relatively low for language modality.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In our previous works (Korostenskaja et al, 2017;RaviPrakash et al, 2017), we showed the feasibility of utilizing conventional machine learning methods for channel response classification by using the whole signal spectrum (not limited to α, β & high γ) and without using the baseline recording. This was one of the first machine learning based approaches in this field with strong results and demonstrated the potential of ECoG-FM signal to be analyzed more accurately compared to conventional signal processing based descriptive methods.…”
Section: Related Work and Existing Critical Challengesmentioning
confidence: 99%
“…In our previous work 23,24 , we showed the feasibility of machine learning methods to perform classification of channel response by using the whole signal spectrum (not limited to α, β & high γ) and without using the baseline recording. This was the first machine learning based approach in this field and demonstrated the potential of ECoG-FM signal to be analyzed more accurately compared to the conventional methods.…”
Section: B)mentioning
confidence: 99%
“…These studies showed that accepting electrodes with a high response in either the gamma band, the beta band, or in both, as potentially eloquent yielded better results than using either band alone, especially in the language cortex. Likewise, machine- and deep- learning approaches ( Prakash et al, 2017 ; RaviPrakash et al, 2020 ) have shown that using the entire frequency spectrum, rather than only the gamma band, yields better mapping results, although it was not made clear which part of the spectrum offered the most additional information. In addition, while there is considerable heterogeneity in the task employed between studies, few studies have directly compared different tasks in the same group of patients.…”
Section: Introductionmentioning
confidence: 99%